Comparative studies of ectomycorrhizae in South African forestry - Theron, J. M.(Jacobus Meeding) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. (Forestry)) -- University of Stellenbosch, 1991.